RUSSIAN PAINTING IN THE SECOND HALF OF THE XIX CENTURY IN THE WEST EUROPEAN AND NATIVE CRITICISM - E. G. Meshcherina (Концепт: философия, религия, культура, 2017)
Analyzing the mainstream of the Russian realistic painting of the second half of the 19th century reflected in the West European press, which covered Russian artists' participation in World Fairs in London (1862; 1872), Vienna (1873) and Paris (1878), the author concludes about multilateral and concerned approach to their arts. The leading publications of that time ("Times", "Daily-Telegraf", "Presse", "France") devoted their pages to long reviews analyzing the works of Russian painters. The problems of Russian painting are described by such famous critics are F. Peht, T Taylor, M. Vachon, J. Klaresi, P. Manz. Reports of the western critics who mentioned indisputable progress of the Russian school in landscape (Shishkin, Aivazovsky, F. Vasiliev, Kuindzhi), genre (Perov, V. Makovsky, Myasoedov), portrait (Perov, Kramskoy) and battle (Vereshchagin) painting, contradicts with the existing stereotype about mainly ethnographic interest in the Russian art of that time. The article also states that the European artistic critics was not homogeneous: German reviewers were interested mostly in religious, battle and national themes, English - painting art and political context, the most welcoming French - portrait and battle. Despite the recognition of the Russian realistic painting in Europe (strength, faithfulness to nature, coloristic achievements), vigorous support of V.V. Stasov, defending the Russian national art, many national journalists and cultural figures kept a scornful attitude towards it. As compared with the Russian critics the evaluation of Russian realists presented by European authors, albeit not without bias and curiosities, in general is more professional and it's of particular interest for modern understanding and interpretation of their works.